2022
DOI: 10.1073/pnas.2201160119
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution of extreme production of variant plant monounsaturated fatty acids

Abstract: Metabolic extremes provide opportunities to understand enzymatic and metabolic plasticity and biotechnological tools for novel biomaterial production. We discovered that seed oils of many Thunbergia species contain up to 92% of the unusual monounsaturated petroselinic acid (18:1Δ6), one of the highest reported levels for a single fatty acid in plants. Supporting the biosynthetic origin of petroselinic acid, we identified a Δ6-stearoyl-acyl carrier protein (18:0-ACP) desaturase from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…These FA can be converted to adipic acid (C6:0), a building block of 6,6-nylon, with an annual production of about 2.5 million metric tonnes in the petrochemical industry. Overexpression of related acyl-ACP desaturase has resulted in very low levels of these monounsaturated FA (Gan et al, 2022).…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%
“…These FA can be converted to adipic acid (C6:0), a building block of 6,6-nylon, with an annual production of about 2.5 million metric tonnes in the petrochemical industry. Overexpression of related acyl-ACP desaturase has resulted in very low levels of these monounsaturated FA (Gan et al, 2022).…”
Section: Monounsaturated Fatty Acidsmentioning
confidence: 99%
“…In addition to the already cited examples of the detection of nebraskanic and wuhanic acids in (Li et al, 2018), an analysis of the leaf lipidome has also yielded 393 molecular species within 23 different lipid classes (Tarazona et al, 2015) that cannot be deduced from the FA composition alone. A very recent article (Gan et al, 2022) report on the exploration of Thunbergia genus, which revealed that numerous species accumulate petroselenic (18:1 D6 ) instead of sapienic acid (16:1 D6 ). Thus, detailed study of a genus may reveal the accumulation of unexpected FAs, resulting from probable evolutionary divergence in the genus.…”
Section: Accounting For Undesired Effectsmentioning
confidence: 99%
“…Photosynthetic organisms, including plants and algae, possess a remarkable ability to harness carbon dioxide and solar energy, enabling them to produce a vast array of complex compounds such as phenolic acids ( Zhou et al., 2021 ), terpenes ( Miller et al., 2020 ), unsaturated fatty acids ( Kokabi et al., 2020 ; Gan et al., 2022 ), and other lipid products ( Zienkiewicz and Zienkiewicz, 2020 ). This inherent capability positions them as highly promising platforms for the sustainable production of valuable biomolecules.…”
mentioning
confidence: 99%